Prosthetic joint infection of the hip and knee due to Mycobacterium species: A systematic review - Santoso, Asep; Phatama, Krisna Yuarno; Rhatomy, Sholahuddin; Budhiparama, Nicolaas Cyrillus (Baishideng Publishing Group Inc, 2022)
BACKGROUND: Mycobacterium species (Mycobacterium sp) is an emerging cause of hip and knee prosthetic joint infection (PJI), and different species of this organism may be responsible for the same. AIM: To evaluate the profile of hip and knee Mycobacterium PJI cases as published in the past 30 years. METHODS: A literature search was performed in PubMed using the MeSH terms “Prosthesis joint infection” AND “Mycobacterium” for studies with publication dates from January 1, 1990, to May 30, 2021. To avoid missing any study, another search was performed with the terms “Arthroplasty infection” AND “Mycobacterium” in the same period as the previous search. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses chart was used to evaluate the included studies for further review. In total, 51 studies were included for further evaluation of the cases, type of pathogen, and treatment of PJI caused by Mycobacterium sp. RESULTS: Seventeen identified Mycobacterium sp were reportedly responsible for hip/knee PJI in 115 hip/knee PJI cases, whereas in two cases there was no mention of any specific Mycobacterium sp. Mycobacterium tuberculosis (M. tuberculosis) was detected in 50/115 (43.3%) of the cases. Nontuberculous mycobacteria (NTM) included M. fortuitum (26/115, 22.6%), M. abscessus (10/115, 8.6%), M. chelonae (8/115, 6.9%), and M. bovis (8/115, 6.9%). Majority of the cases (82/114, 71.9%) had an onset of infection > 3 mo after the index surgery, while in 24.6% (28/114) the disease had an onset in ≤ 3 mo. Incidental intraoperative PJI diagnosis was made in 4 cases (3.5%). Overall, prosthesis removal was needed in 77.8% (84/108) of the cases to treat the infection. Overall infection rate was controlled in 88/102 (86.3%) patients with Mycobacterium PJI. Persistent infection occurred in 10/108 (9.8%) patients, while 4/108 (3.9%) patients died due to the infection. CONCLUSION: At least 17 Mycobacterium sp can be responsible for hip/knee PJI. Although M. tuberculosis is the most common causal pathogen, NTM should be considered as an emerging cause of hip/knee PJI.